Assessing the Possibility of Changes in a Company’s Competitive Potential Using the Strategic Reflection Method - Rawski, Marek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The purpose of the paper is to show that the characteristics and properties of strategic reflection method (its third stage, to be precise) effectively identify potential opportunities to develop competitive business components according to the expectations formulated by stakeholders. Four groups are assessed: the owners of shares, customers, employees and suppliers. The paper’s theses are examined, presenting a fragment analysis for the real case of companies from the food industry that are active on the Polish market.